2022
DOI: 10.1186/s13075-021-02690-w
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic alterations in human annulus fibrosus correlate with progression of intervertebral disc herniation

Abstract: Background Intervertebral disc (IVD) herniation is characterized by annulus fibrosus failure (AF) in containing the nucleus pulposus (NP). IVD herniation involves cellular and extracellular matrix (ECM) alterations that have been associated with tissue fibrosis, although still poorly investigated. Methods Here, fibrotic alterations in human AF were evaluated, by characterizing the herniated ECM. Human AF samples (herniated lumbar IVD (n = 39, age 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…106 When the spine is subjected to axial compression, the tightly packed annulus fibrosus absorbs pressure from the NP to the AF wall. 107 Therefore, AF degeneration accelerates the progression of IDD.…”
Section: Mtor Signalling In Af and Cepmentioning
confidence: 99%
“…106 When the spine is subjected to axial compression, the tightly packed annulus fibrosus absorbs pressure from the NP to the AF wall. 107 Therefore, AF degeneration accelerates the progression of IDD.…”
Section: Mtor Signalling In Af and Cepmentioning
confidence: 99%
“…Mechanical factors, including compressive loading, shear stress, and vibration, can all contribute to disc degeneration [ 20 ]. In addition, structural failure (e.g., annular tear, bulging disc) also associates with IVD degeneration [ 20 , 21 ]. Inadequate metabolite transport across the end plate, aging, genetics, and metabolic disorders (e.g., obesity, diabetes) may likewise contribute to disc degeneration [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disparity in fibril changes might be due to differences in the species and natures of IDD. Thinner and disorganized collagen I fibers are also detected in fibrotic alteration of AF [ 64 ]. He et al recently reported that collagen fibrils were thicker in aging than in punctured IVDs [ 7 ].…”
Section: Matrices In Np Fibrosismentioning
confidence: 99%
“…In addition to a change in local cell entities, reports have suggested the infiltration of extrinsic cells. Accumulation of macrophage- (CCR7 + , CD163 + [ 4 ] and CD68 + [ 69 ]) and myofibroblast-like (α-SMA + ) [ 6 , 64 , 70 ] cells were documented in degenerative NP and AF. Additionally, the migration of bone marrow-derived MSCs into NPs were noted in a mouse tail-looping IDD model [ 71 ].…”
Section: Cell Composition In Np Fibrosismentioning
confidence: 99%